Analisis Indeks Produktivitas Lahan untuk Pengembangan Tanaman Pangan di Bagian Hilir Daerah Irigasi Kampili - Akbar, Muh.; Rasyid, Burhanuddin; Laban, Sartika (Jurnal Ecosolum, 2019)
The large population growth of Indonesia encourages the transition of the function of agricultural land into non-agricultural land. The demand for land from time to time always increased, while the available land limited in number. This caused the conversion of agricultural land into non-agricultural land. This phenomenon certainly could bring serious problems. This study aimed to determine the land productivity index for rice and green beans cultivation and to find out the factors that influence production. The productivity indexes analyzed based on the Storie Approach. Soil sampling was carried out by an open grid method divided based on five land map units which spread across three different villages in Kampili irrigation area. The results of the study indicate that the highest productivity index is shown in SPT 5 where the productivity index is 47 and the lowest productivity index is shown in SPT 2 where the productivity index is 21,6. The land productivity index in the downstream of the Kampili irrigation area, which is located in the district of West Bajeng is poor to sufficient level. The low value of land productivity was strongly influenced due to poor soil quality, especially soil chemical properties. The results of the laboratory analysis show that nutrients in those areas are low.